INFLUENCER MARKETING SELECTION STRATEGY IN ORGANIZING THE GRAND OPENING MINI MARKET PROMOTIONAL ACTIVITIES PASARPRIMA YOGYAKARTA - Chriswardana Bayu Dewa; Lina Ayu Safitri (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
This study aims to analyze the influencer marketing selection strategy in organizing the grand opening promotional activities at the Pasarprima mini market, Yogyakarta. This research is a qualitative research with data collection methods used by interviews, observation and literature study. The result of this research is that using social media as the distribution of promotional content by using influencers can save costs because it has a high effectiveness from the results of creative content that is carried out to get the attention of the target market. From this study, the authors only look at the effectiveness of using influencers only from the amount of exposure (viewers, likes, followers and engagement) generated. For the next promotional activity, the marketing selection strategy can add other elements such as the number of sales and visitors during promotional activities. Keywords: Social Media Marketing, Strategy, Influencer